TAX PLANNING APPLICATION TO MINIMIZE INCOME TAX (Case Study at INDOBENT Ltd. Pacitan Branch) - Aflah, Muhammad; Rustam, Akie Rusaktiva (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study discusses how Indobent Ltd. which is a company engaged in the field of mineral processing bentonite in tax planning to take advantage of opportunities that can still be done to make tax savings. Therefore the tax planning thing still did not disobey authorized regulation descended by the goverment.In general terms, this research discussed deductible expense elements and non-dedutible expense elements. These terms take on purpose for determining tax planning strategy on changing expenses that can not be eliminated before as reduceable income taxes.The research is a kind of observation that used qualitative description method with case study approach. The case study contributed in making comparable reasoning about income tax payment with and without tax planning treatment.TheÂ research summarizes that Indobent Ltd. did not performed optimum tax planned yet. Many opportunities that can be included for tax savings was still unforeseen become the cause. Reducing amount of tax payment could be reached with implementing tax planning strategy on using beneficiary from opportunities included changing non deductible expense element to deductible expense such as giving employeeâ€™s consumption, recreation, and employee achievement, for example, as subsidies reather than costs and award a bonus, adding the cost of education and human resources development, determining the depreciation method for fixed assets, also arrange nominative list and detailed list for entertainment expense. Â Keywords: Tax planning, Planning strategies taxation, Tax saving